Les personnes âgées immigrées à l’épreuve du Successful Aging - Aurélien Martineau; Mathilde Plard (Cybergeo, 2018)
Since the mid-20th century, scientists have constantly examined the conditions for healthy aging. Successful Aging as a paradigm has gradually spread far beyond the scientific sphere. Access to « successful-aging » has become a collective purpose as a policy reference in our contemporary societies. As people get older in their host country, immigrants have to conform to the dominant gerontological models. Therefore, the « success » of elderly migrants’ aging in France represents a political and public health objective. This article aims at examining the links between migration and aging in order to better understand the social and spatial issues associated with the elderly immigrants « successful-aging » in France. To deal with this problem, a literature review on the aging conditions of immigrants in France (based on a corpus of 75 references) was completed. This article combines the results of this state of the art by analyzing the situations of elderly migrants through two of the main components of Successful Aging (1. Their health status and 2. Their social networks and commitment in social life). The results demonstrate that the « success » of aging is more complex for elderly migrants compared to the normative ideal of « successful-aging ». While it is necessary to avoid a generalized view of their situations, the living conditions in France and the discontinuities encountered expose some of these groups to significant difficulties in old age. Research in geography is necessary to spatialize the different aging experiences of immigrants within their own territories.